Metoda analizy statystycznej efektu kolmatacji i filtrowania - Borowik, S.; Redmer, B. (Engineering Transactions, 1968)
The problem of analysis of the filtration effect of liquids and gases in hydraulic and pneumatic installations is essential for the phenomena accompanying the colmatage of particles of a suspension in a porous wall.The method of statistical analysis of these phenomena proposed in the present paper is based on a simplified model of the colmatage process consisting in assuming that the particles of the liquid suspension considered (and characterized by a distribution density function) are sphericaland that the structure of the porous body (described by two distribution density functions of pores: "geometric" and "hydraulic") is perfect.The probability of meeting a pore of definite dimension is assumed to be independent of the size of the particle. As a result the equations of the colmatage and filtration are obtained. It is shown also that the filtration characteristic depends only on the geometric and hydraulic propertiesof the porous wall (Eq. 3.10).The experimental part of the paper contains a discussion of the results of tests of the internal structure of filters of sintered metal balls and the approximation to the distribution of pores in such filters by the Rayleigh distribution. According to the relation (3.10) derived diagrams of filtration characteristics of four filters are plotted by integrating the distribution density function of pores.